Developing concept-situation skills of the educable mentally retarded through picture drama primary level - Palmaira, Marcelina C. 1929-; Adorio, Mercedes P. (1974)
The study delved into the conceptualization skills of the educable mentally retarded, the importance of picture drama in teaching conceptualization skills among the educable mentally retarded, the different social skills which can be effectively taught with the use of picture drama, and classroom approaches in the teaching of conceptualization skills. The use of picture drama offers great opportunities in improving learning. Through this approach, the educable mentally retarded sees the anti-social behavior, and the cause and effect. Thus, he is helped in making his own evaluation of the event.
Vita.
Thesis (Master of Arts in Teaching - Special Education : Mental Retardation)--University of the Philippines, Diliman.
Keywords: Children with mental disabilites -- Education (Primary) -- Philippines -- Manila; Picture interpretation -- Philippines -- Manila; Picture perception -- Philippines -- Manila; Visual perception in children -- Philippines -- Manila; Pictures in education -- Philippines -- Manila; Special education -- Philippines -- Manila